Partisipasi Perempuan Pedagang Kakilima Dalam Meningkatkan Ekonomi Rumah Tangga Sebelum Dan Setelah Adanya Covid-19 - Emiliana Martuti Lawalu; Maria Klarista Goba (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2020)
This study pretend to explore the question on who we mean with female vendors? They are females whose model of trade is using small stand in the traditional market. In facts, large contributions they contributed to household economy in terms of income, expendeture, and saving haven’t been denied. Whilst supporting and inhibiting factors are always in common and come together. There are two goals of the study. To capture the income, saving and expendeture of the females vendors and the sircumstance of household economy before and during the Covid-19. In addition, the study is to detect supporting and inhibiting factors during they are undertaking the roles belong to them. By using 50 informan of female vendors in traditional market of Oeba as research subject, the study are developed with descriptive-qualitative analisis method. The results showed that Covid-19 has brought effects to the female vendors. Unfortunately, their contributions to household economy in terms of income, expenditure, and saving during Covid-19 aren’t comensurate with that of before. Supporting factors are emerging through several factors such as self-motivation, economical and environmental need and inhibiting factors such as income decreased, much more competition, and poor in trade experience. Much more hope to government in order to give more concern on trade facilities for female vendors in traditional market, security and control to the market facilities which are not deserve to use in order to be repaired. Vendors and buyers are hoped to obey to government’s health protocol of Covid-19.